Electronic transport on carbon nanotube networks : a multiscale computational approach - Pereira, Luiz Felipe C. (Trinity College (Dublin, Ireland). School of Physics, 2011)
Carbon is arguably the most versatile of chemical elements. For the last 25 years research on carbon nanostrutures has been one of the most active areas of science. Carbon-based nanoelectronics is the most promising alternative to replace the ageing silicon-based technologies. In particular, carbon nanotubes present remarkable physical properties such as very low electrical resistance and very high mechanical strength.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.